Varietas Kelapa Dalam Unggul Spesifik Gorontalo - BAMBANG HELIYANTO; ELSJE T. TENDA (Pusat Penelitian dan Pengembangan Perkebunan, 2010)
High Yielding Coconut Tall Varieties Specific for Gorontalo The major constraint for coconut development program in Indonesia, including Gorontalo Province is the lower crop productivity i.e merely 1 ton copra/ha/year. Increased coconut production and productivity must be done hand in hand with coconut replanting program. To support the program, the use of high quality planting material is required. There are two options available in this matter. First, by utilizing the available coconut tall high yielding varieties suitable for agroclimate similar to Gorontalo (dry climate). Second, or most preferably, utilizing the high yielding local tall coconut cultivars. Preliminary evaluation by local estate officer indicated that there are some local coconut tall cultivars (ca. 4 cultivars) that had both high yield and oil content. This research was therefore aimed at further assessing these four promising local cultivars. Evaluation was done on those pre-determined populations in two phases, for three years consecutively, from 2006 to 2008. Parameter observed include morphological, yield of copra and its components, physiological and chemical characters as well as field resistance to pest. Results of evaluation, conducted by the ICOPRI and Dishutbun Gorontalo, confirmed that two cultivars, namely, Kelapa Dalam Molowahu (DMU) and kelapa Dalam Kramat (DKT) could be considered as two high yielding cocconut tall cultivars specific for Gorontalo. These two cultivars exhibited high productivity (above 3 ton copra/ha/year) and possess high oil content (above 64%). These cultivars have formally been released as new varieties by Minister of Agriculture in Desember 2009, to be used for high quality planting material for coconut development program in Gorontalo.